PENERAPAN TEORI SISTEM HUKUM DALAM PERTANGGUNGJAWABAN PIDANA TINDAKAN OBSTRUCTION OF JUSTICE OLEH APARAT KEPOLISIAN - Gabrielle, Sabrina; Sumanto, Listyowati (Ensiklopedia of Journal, 2025)
This study examines the phenomenon of obstruction of justice by police officers in Indonesia, focusing on the application of Lawrence Friedman's legal system theory. In the context of a state governed by the rule of law, the principles of the supremacy of law and justice are often threatened by acts of obstruction of justice committed by law enforcement officials themselves. This study identifies various forms of obstruction of justice, such as the destruction of evidence and intimidation of witnesses, as well as their impact on public trust in the judicial system. Using Friedman's theory, the analysis focuses on three main elements: legal structure, legal substance, and legal culture. This study uses a descriptive normative legal research method. Secondary data is analyzed qualitatively. Conclusions were drawn using deductive logic. The results of the study show that weaknesses in internal oversight, ambiguity in legal substance, and a culture of solidarity among police officers contribute to the practice of obstruction of justice. This study recommends the need for comprehensive reform in the oversight structure, strengthening of legal substance, and transformation of legal culture to improve accountability and transparency in law enforcement in Indonesia.Keywords: obstruction of justice; criminal liability; legal system theory